Spatial clusters of daily tobacco consumption before and after a smoke-free policy implementation. (July 2021) - Vallarta-Robledo, Juan R.; Sandoval, José Luis; De Ridder, David; Ladoy, Anaïs; Marques-Vidal, Pedro; Humair, Jean-Paul; Cornuz, Jacques; Probst-Hensch, Nicole; Schaffner, Emmanuel; Stringhini, Silvia; Joost, Stéphane; Guessous, Idris
Abstract: This study assessed the spatial dependence of daily tobacco consumption and how it is spatially impacted by individual and neighborhood socioeconomic determinants, and tobacco consumption facilities before and after a smoke-free implementation. Individual data was obtained from the Bus Santé, a cross-sectional survey in Geneva. Spatial clusters of high and low tobacco consumption were assessed using Getis-Ord Gi*. Daily tobacco consumption was not randomly clustered in Geneva and may be impacted by tobacco consumption facilities independently of socioeconomic factors and a smoking ban. Spatial analysis should be considered to highlight the impact of smoke-free policies and guide public health interventions. Highlights: Spatial clusters of high and low tobacco consumption were observed in Geneva. The smoking ban did not modify the geographic distribution of tobacco consumption. Tobacco consumption facilities may impact spatial clusters of tobacco consumption. Spatial analysis should be considered to guide and assess public health policies.